2021
DOI: 10.3389/fvets.2021.674973
|View full text |Cite
|
Sign up to set email alerts
|

Free-Living Aquatic Turtles as Sentinels of Salmonella spp. for Water Bodies

Abstract: Reptile-associated human salmonellosis cases have increased recently in the United States. It is not uncommon to find healthy chelonians shedding Salmonella enterica. The rate and frequency of bacterial shedding are not fully understood, and most studies have focused on captive vs. free-living chelonians and often in relation to an outbreak. Their ecology and significance as sentinels are important to understanding Salmonella transmission. In 2012–2013, Salmonella prevalence was determined for free-living aqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Since sex and species are potential confounding variables, these results should be interpreted with care. The prevalence of Salmonella in several wild turtle species in the US was significantly higher in females than in males (62). This could potentially explain the differences observed in the current study, but it would require equal representation of both sexes in all three species.…”
Section: Discussionmentioning
confidence: 66%
“…Since sex and species are potential confounding variables, these results should be interpreted with care. The prevalence of Salmonella in several wild turtle species in the US was significantly higher in females than in males (62). This could potentially explain the differences observed in the current study, but it would require equal representation of both sexes in all three species.…”
Section: Discussionmentioning
confidence: 66%
“…Although it is not one of the leading serovars causing human salmonellosis, there is increasing concern with the emergence of multidrug resistance particularly associated with this serovar ( Milton et al, 2018 ; Al-Gallas et al, 2021a , b ). On the other hand, S. Rubislaw has been mainly detected in environmental samples ( Maurer et al, 2015 ), and various free-living animals ( Potter et al, 2011 ; Rush et al, 2020 ; Hernandez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella enterica is a member of the Salmonella spp., as sentinels of Salmonella spp. invasion, aquatic turtles are highly susceptible to accumulating Salmonella present in water and cause their disease [ 50 ]. Raidal et al [ 51 ] also found that salmonellae can cause systemic illness and death in green sea turtles.…”
Section: Discussionmentioning
confidence: 99%